Vitamin D, Glutamine, Evidence-Based Medicine, and Close Staff Supervision Reduce Mortality Rate at a Level I Trauma Center - L Ray Matthews; Yusuf Ahmed; Omar K Danner; Golda Kwaysi; Dianne Dennis-Griggs; Keren Aviva Bashan-Gilzenrat; Jonathan Nguyen; Ed W Childs; Nekelisha Prayor; Peter Rhee; Kenneth L Wilson (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Background: It has been estimated that over 400,000 patients die each year from medical errors in the United States. The purpose of this study was to investigate the impact of vitamin D (a steroid hormone and immune modulator) and glutamine supplementation, evidence- based medicine, and close staff supervision on hospital mortality rate in trauma patients. We hypothesized that vitamin D and glutamine supplementation, evidence-based medicine, and close staff supervision has an appreciable or measureable effect in reducing the hospital mortality rate in critically injured patients admitted to surgical intensive care units and to surgical floors.  Study Design: We performed a retrospective study of 6,258 trauma patients listed in the trauma registry who were admitted to the Trauma Service at Grady Memorial Hospital, a Level I trauma center, between January 1, 2000 and December 31, 2011. The analysis compared two groups: standard care treatment group (Control Group)) versus the evidence-based medicine treatment group (Evidence -Based Medicine Group). Trauma patients admitted from 2000-2006 (Control Group, n=3,285) were treated with standard (usual) care. Trauma patients admitted from 2007-2011 (Evidence-Based Medicine Group, n=2,973) were managed with standard care plus vitamin D and glutamine supplementation, evidence -based medicine, and close staff supervision. The primary outcome was mortality rate of the Control Group versus the Evidence-Based Medicine Group.  Results: Our study did not find any statistical difference between standard/usual treatment and evidence-based treatment groups in terms of number of admitted patients (3285 Vs. 2973), gender (76% male in both groups, and 24% female in both groups), age distribution (89% were ages between 15 to 55 in standard/usual group Vs. 89% in evidence based group), trauma type (blunt trauma; 66.6% in both groups, penetrating trauma; 33.4% in both groups) and measured blood alcohol levels (19.0% in both groups had >8mg/dl) However the overall mortality rate for the trauma patients treated with standard/usual care group was 10.7% compared to 4.1% for the trauma patients treated with evidence-based medicine, a 6.6% absolute reduction in mortality (RRR, 61.6%, 95%CI, 2.26-3.46,P<0.0001).  Conclusion: Our study suggested that, implementation of evidence-based medicine methodology significantly reduces the mortality rate among the trauma patients treated in the Evidence-Based Medicine Group. Further studies are warranted.